2021
DOI: 10.3389/fonc.2021.721785
|View full text |Cite
|
Sign up to set email alerts
|

Role of Extracellular Vesicles on Cancer Lymphangiogenesis and Lymph Node Metastasis

Abstract: Lymph node metastasis (LNM) of tumors is an established indicator of poor prognosis in patients. Tumor-associated lymphangiogenesis is a key step in LNM and has gained much attention. However, currently, there is no anti-tumor lymphangiogenesis drug used in clinical practice. Recently, studies on extracellular vesicles (EVs) have shown that different types of cells in the tumor microenvironment can release EVs that encapsulate a variety of molecules, including proteins, nucleic acids, and metabolites. Lymph en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Currently, exosomes as cellular communication mediators have been shown to be involved in modulating sequential metastatic processes ( 22 ). Most studies have shown the importance of lymphangiogenesis contributing to LNM and exosome-mediated lymphangiogenesis ( 23 , 24 ) but the role of lymphangiogenesis in LNM is still controversial ( 25 ). Therefore, from a different perspective, we revealed a novel mechanism whereby lymphatic metastatic GC cell-exosomes directly conferred the LNM phenotype on primary GC cells depending on FAO reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, exosomes as cellular communication mediators have been shown to be involved in modulating sequential metastatic processes ( 22 ). Most studies have shown the importance of lymphangiogenesis contributing to LNM and exosome-mediated lymphangiogenesis ( 23 , 24 ) but the role of lymphangiogenesis in LNM is still controversial ( 25 ). Therefore, from a different perspective, we revealed a novel mechanism whereby lymphatic metastatic GC cell-exosomes directly conferred the LNM phenotype on primary GC cells depending on FAO reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…The TDLN modifications mentioned above, induced by tumor-secreted factors, prepare the LN for the arrival of cancer cells, creating the pre-metastatic niche ( 16 ). Although signals involved in this TDLN preparation remain to be completely understood, tumor-derived extracellular vesicles (TEVs) can serve as carriers of multiple tumor-derived molecules (nucleic acids, proteins and metabolites) that play a key role in the remodeling of TDLNs ( 176 , 177 ). TEVs can be transported by LVs to TDLNs, where they may be retained.…”
Section: Cancer -Lymphatic- Immune Cell Crosstalk During Metastatic D...mentioning
confidence: 99%
“…Given that lymphangiogenesis plays a critical role in LN metastasis, it may be viable to treat cancers using an anti-lymphangiogenesis strategy ( 104 ). Some receptor tyrosine kinase inhibitors may exert negative effects on tumor-related lymphangiogenesis (and LN and distant organ metastases) by targeting the VEGF-C–VEGFR3 signaling pathway ( 105 , 106 ).…”
Section: Therapy Based On Anti-lymphangiogenesis Strategymentioning
confidence: 99%